Site-dependence of relationships between photoluminescence and applied electric field in monolayer and bilayer molybdenum disulfide - Nozaki, Junji; Nishidome, Hiroyuki; Maruyama, Mina; Okada, Susumu; Kusaba, Satoshi; Tanaka, Koichiro; Ueno, Keiji; Yomogida, Yohei; Yanagi, Kazuhiro (Japanese Journal of Applied Physics, 2019)
Understanding of the optical properties at a specific site in two-dimensional materials is important for their opto-electronic applications. Here, we investigated the site dependence of the relationship between the photoluminescence spectrum and an electric field in monolayer and bilayer molybdenum disulfide (MoS2) using a technique combining scanning near-field optical microscopy (SNOM) and a bias voltage application from the SNOM cantilever. We revealed the difference between two factors, doping level and PL quantum efficiency, at each site and their significant influence on the relationship between PL intensity and bias voltage, evaluating the specific influences of the two factors on the relationship. In addition, we clarified that carrier injection at a site in the bilayer region induces an increase in the A peak intensity and a decrease in the I peak, discussing the background in view of theoretical calculations.